Ist es notwendig polnische Nasalvokale zu untersuchen? - Molenda Aleksandra; Artur Tworek (Linguistische Treffen in Wrocław)
The declared aim of this article is to draw attention to Polish nasal vowels. The motivation for its creation is the lack of complexity in the description of this subsystem noted in the specialised literature. The descriptions of Polish nasal vowels offered in the specialised literature were usually prepared within the framework of Polish phonology as a whole. The focus of characterisations of Polish nasal vowels based on the phonetic perspective, on the other hand, is usually on nasal consonants (cf. Dukiewicz 1967, among others). The comparative publications also focus primarily on the phonological descriptions of this subsystem. At this point, the need for a complex phonetic description of Polish nasal vowels in comparison with those languages in which speech sound inventories also contain such subsystems becomes apparent. In favour of the complexity of this description of Polish nasal vowels, we propose the following perspectives: phonetic, phonological, sociophonetic, didactic and typological (comparative). Approaching the phenomenon of nasal vowels not only from a segmental perspective but also from the perspective of the higher levels of language structure (expression, text) would allow the abstractness of phonological systems to be adapted to the realities of speech. This adaptation is hardly possible without a systematic explication of the pronunciation varieties. In addition to the question of articulatory variants, there is also the question of co-articulatory and dialectal or regiolectal factors as well as idiolectal tendencies in the realisation of nasal vowels. A concrete communicative consonant situation in which the nasal vowels discussed in the article are realised should also be taken into account.